Experimental Study of Concrete by Partial Replacement of Coarse Aggregate by E-Waste: Exploring the Use of E-Waste as a Partial Replacement for Coarse Aggregate in High Grade Concrete (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The E-Waste generation is a serious issue now a days in whole world. Recently the government of India has banned the use of plastic as it is hazardous to the human being and also cannot be disposed or reused easily. By generation of astounding 1.85 million tonne of E-waste annually, India has become the 5th largest e-waste producing country in the world. It consists of PCB boards, computer, TV, etc. It is helpful by using the E Waste rather than the naturally occurring of stone metal. In this paper the analysis of high grade concrete is been done i.e. M35 by adding non-metallic E-Waste (Plain PCB boards) in proportion of 0, 5, 10 15 respectively.